Learning assessment skill at school: a strategic asset for life - Montalbetti, Katia (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2020)
Assessment skill is considered strategic to govern complexity and to direct oneself in longlife and longwide learning process being a highly transversal skill. Consequently, all educational and training contexts, and among them in particular schools, should encourage and promote its development; instead of this assessment skill rarely is an explicit objective in teaching practice. In innovative contexts students can be asked to carry out an assessment exercise but without an adequate training this request can be risky. This is particularly true in student assessment of teaching where the inversion of roles can negatively influence the quality of educational relationships. To full exploit the educational potential of assessment practices in the school context, it is necessary to relaunch an assessment agreement within a framework of commitment and co-responsibility between teachers and students.